Changes in prescription pain medication and intra-articular corticosteroid utilization after intra-articular bio-fermentation derived hyaluronic acid use in patients undergoing multimodal pain management. (1st January 2022) - Nicholls, Mathew; Niazi, Faizan; Nelson, Winnie W.; Lau, Edmund; Kurtz, Steven M.; Ong, Kevin L.
Abstract: Background: Multiple interventions may be used to treat symptomatic knee osteoarthritis (OA), but concerns have been raised about the safety and efficacy of some therapies. Clinical trials have shown that hyaluronic acid (HA) can provide pain relief up to 6 months and possibly to 12 months, while real-world data has shown that pain medication and intra-articular corticosteroid (CS) injection utilization are reduced within 6 months after HA. Objective: To examine changes in prescription pain medication and CS utilization during 1 year after multimodal therapy that included high molecular weight, bio-fermentation derived HA (Bio-HA) use for knee OA. Methods: Commercial and Medicare Supplemental claims data (IBM MarketScan Research Databases) (1 January 2012, through 31 December 2018) was used to identify unilateral Bio-HA patients using multimodal therapy (any combination of CS injection, opioids, and non-opioid pain medication). Monthly therapy utilization was compared in the 12 months after Bio-HA therapy initiation to the 4-month intra-multimodal period. Results: A total of 13, 999 patients underwent Bio-HA therapy with concurrent multimodal therapy. The number of filled opioid prescriptions decreased from 2, 913.0/month to 2, 861.5/month after Bio-HA, with a reduction in mean monthly prescriptions from 0.60 to 0.43 per user ( p  < 0.001). A number of opioid days supplied also decreased from 48, 914/month to 39, 730/month, with a decrease from 10.1/month to 6.0/month per user ( p  < 0.001). Bio-HA patients had prescription pain medication-free days for 71% of the time post-multimodal period compared to 53% during the intra-multimodal period ( p  < 0.001). The proportion of patients with CS injections after Bio-HA decreased from 53.8% to 29.6% ( p  < 0.001). Total monthly CS injections decreased from 2, 292 to 663. Conclusions: Our data suggest that high molecular weight Bio-HA, as part of multimodal therapy, may be effective in providing longer-term pain relief with the reduction in pain therapy (CS injections and opioids) and increase in prescription pain medication-free days.